Long‐Term Follow‐Up of Superior Vena Cava–Right Atrium Spontaneous Conduction Block Line Durability Using the White‐Line Approach of Extended Early Meets‐Late Rate Tools - Yoshiaki Mizunuma; Masao Takahashi; Takafumi Sasaki; Koichiro Yamaoka; Hirofumi Kujiraoka; Tomoyuki Arai; Rintaro Hojo; Seiji Fukamizu (Journal of Arrhythmia)
ABSTRACT Background Superior vena cava (SVC)–right atrium (RA) spontaneous conduction block occurs in some patients. We demonstrated a novel approach for SVC isolation using visualization of the SVC–RA conduction block line as a white line with the extended early meets‐late (EEML) tool of the CARTO system. The long‐term durability of SVC isolation using white line has not been investigated. Methods Overall, 200 patients who underwent SVC isolation as atrial fibrillation therapy or additional procedures between May 2015 and April 2024 were included. We created an activation map of sinus rhythm, adjusted the EEML settings, and confirmed the white line. In the presence of a white line, we performed SVC isolation using the white line (block group); in its absence, we conducted encircling SVC isolation (nonblock group). If additional procedures were needed at follow‐up, repeat sessions were performed to identify the treatment targets, and SVC–RA mapping was performed. SVC–RA block line durability was defined as the SVC isolated area by voltage map at the additional session, including the white line of the first session. The SVC reconduction number between the two groups was compared, and SVC–RA spontaneous block line durability was confirmed in the block group. Results Thirty‐one of 200 patients underwent additional procedures and follow‐up SVC–RA mapping. The chronic SVC reconduction ratio did not differ significantly between the two groups. SVC–RA spontaneous block line durability was maintained in all patients in the block line group (block group 12/12 [100%]). Conclusion SVC–RA spontaneous block visualized by using the white‐line approach of EEML tools had durability in the chronic phase.